Governança nas regiões de saúde: um estudo na Comissão Intergestores Regional (CIR) de saúde da Paraíba - Vitorino, Salmon Carlos (2018)
The research has as its theme the analysis of the main aspects that populate the public health policies, with emphasis on the process of governance and collaboration between public agents that work in the Regional Interagency Commission (RIC), more precisely within the perimeter that circumscribes the Region of health of Paraíba. From the technical and political perspective exposed, the main norms related to the Unified Health System (UHS) are based on the Federal Constitution of 1988, whose norms encourage the relationship of cooperation between institutions and public agents. Aiming to understand the process of collaborative governance based on the perceptions of the public agents involved in the meetings of this commission. Regarding the methodology, it can be characterized as a qualitative, basic, descriptive and exploratory research, occurring through bibliographical and documentary research, having as instruments of data collection the application of a semistructured questionnaire and direct observation, whose subjects were the health secretaries and their respective technicians. The explanatory model of Collaborative Governance, elaborated by Ansell and Gash (2008), proved effective as an analytical research tool, since it guided the data collection and the verification of the perception of the public health agents that are members of this commission. The results show that collaboration should be seen as a piece intertwined with political activity and the set of techniques in Public Management, serving as a guide to the efficiency of paths mapped in favor of the quality of management practices and performance in UHS, since the process is still incipient, but has been evolving, requiring investment in the improvement and qualification of some of the public health agents of RIC surveyed.